A simple endogenous growth model with endogenous fertility and environmental concern. (20th February 2017) - Marsiglio, Simone
Abstract: We analyze the implications of endogenous fertility choices on both economic and environmental performances in a stylized AK‐type growth model. Differently from what traditionally assumed in the growth and environment literature, we allow pollution to be not only a by‐product of productive activities by firms but also a result of households' behavior, as suggested by the celebrated IPAT equation. We show that along the balanced growth path equilibrium, economic growth may be non‐monotonically related to the population growth rate as agents care for the environment; moreover, demographic policies can be used both to achieve win‐win outcomes (simultaneously fostering economic growth and improving environmental quality) and to stabilize the otherwise non‐monotonic economic and population growth relationship.